2001
DOI: 10.1073/pnas.151249098
|View full text |Cite
|
Sign up to set email alerts
|

Old yellow enzyme: Reduction of nitrate esters, glycerin trinitrate, and propylene 1,2-dinitrate

Abstract: The reaction of the old yellow enzyme and reduced flavins with organic nitrate esters has been studied. Reduced flavins have been found to react readily with glycerin trinitrate (GTN ) (nitroglycerin) and propylene dinitrate, with rate constants at pH 7.0, 25°C of 145 M ؊1 s ؊1 and 5.8 M ؊1 s ؊1 , respectively. With GTN, the secondary nitrate was removed reductively 6 times faster than the primary nitrate, with liberation of nitrite. With propylene dinitrate, on the other hand, the primary nitrate residue was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
40
0
1

Year Published

2002
2002
2017
2017

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(42 citation statements)
references
References 32 publications
1
40
0
1
Order By: Relevance
“…Similar enzymes are responsible for nitrate ester degradation by Agrobacterium radiobacter (Snape et al, 1997) -' nitrate ester reductase ' -and by strains of Pseudomonas fluorescens and Pseudomonas putida (Blehert et al, 1999) -' xenobiotic reductases'. OYE also catalyses the cleavage of nitrate esters, albeit at a slower rate than these bacterial enzymes, probably via a radical-based mechanism (Meah et al, 2001).…”
Section: An Old Yellow Enzyme Family Of Flavoproteinsmentioning
confidence: 99%
“…Similar enzymes are responsible for nitrate ester degradation by Agrobacterium radiobacter (Snape et al, 1997) -' nitrate ester reductase ' -and by strains of Pseudomonas fluorescens and Pseudomonas putida (Blehert et al, 1999) -' xenobiotic reductases'. OYE also catalyses the cleavage of nitrate esters, albeit at a slower rate than these bacterial enzymes, probably via a radical-based mechanism (Meah et al, 2001).…”
Section: An Old Yellow Enzyme Family Of Flavoproteinsmentioning
confidence: 99%
“…All four enzymes exhibit similar properties in that they are oxidoreductases that convert GTN to glycerol dinitrate and nitrite by using either NADH or NADPH as a reducing agent, and they are members of the old yellow enzyme (OYE) family of oxidoreductases (27). Crystallization of OYE in the presence of an inhibitor, p-hydroxybenzaldehyde, and subsequent mutagenesis studies have shown that are involved in OYE's activity toward its substrates, including substituted phenols, cyclohexanone, and GTN (6,8,11,15). The aim of the work presented here was to establish unequivocally the involvement of flavin mononucleotide (FMN) as a prosthetic group in the action of NerA on GTN, the kinetic form of the reaction, and the effect on the kinetics of mutations at the corresponding His, Asn, and Tyr residues.…”
mentioning
confidence: 99%
“…The catalytic residues found in OYE are conserved in EasA, as was predicted from sequence alignments (Cheng et al, 2010a). A mechanism for the reduction of chanoclavine-I aldehyde to dihydrochanoclavine aldehyde has been proposed (Cheng et al, 2010a) based on the extensive literature for old yellow enzymes (Brown et al, 1998(Brown et al, , 2002Fox & Karplus, 1994;Karplus et al, 1995;Kohli & Massey, 1998;Meah et al, 2001;Williams & Bruce, 2002;Xu et al, 1999). In this mechanism, the reductive half reaction allows reduction of the FMN by NADPH.…”
Section: Overall Structure Of Easamentioning
confidence: 95%